PENERAPAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA MENGENAI DANA DESA UNTUK PEMBANGUNAN DESA BERKELANJUTAN (STUDI DESA SUKOSARI KECAMATAN JUMANTONO KABUPATEN KARANGANYAR) - Firdausy, Adriana Grahani; Anjar, Bayu (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2017)
Sukosari Village is the one located in Karanganyar Regency obtaining Village Fund. It is the Village Fund that can be managed according to Articles 4-7 of Karanganyar Regent’s Regulation Number 41 of 2015 about Technical Instruction of Village Fund Use. The Distribution of Sukosari Village Head’s Regulation Number 4 of 2015 about The Amendment to The Elaboration of Income and Expense Budget for Sukosari Sub District of Jumantono Sub District in Fiscal Year 2015 was conducted to disburse the Village Fund more smoothly.The result obtained was that Village Fund that has come into the village account has been used corresponding to the Article 8 through Article 15 of Karanganyar Regent’s RegulationNumber 41 of 2015 about Technical Instruction of Village Fund Usedescribes the use priority Village Fundprioritized in the attempt of financing the community development and empowerment with good governance principle in which there were some elements of good governance that could support the sustainable village development.